TNF Receptor–Associated Periodic Syndrome: An Analysis of a Slovakian Cohort of TRAPS Patients - Slenker, Branislav; Banovcin, Peter; Hrubiskova, Katarina; Vargova, Veronika; Bobcakova, Anna; Gensor, Dusana; Jurkova, Eva Malicherova; Kapustova, Daniela; Kapustova, Lenka; Markocsy, Adam; et al. (Archives of Rheumatology, 2025)
Background/Aims: Tumor necrosis factor receptor–associated periodic syndrome (TRAPS) is an autosomal dominant systemic autoinflammatory disease caused by mutations in the TNFRSF1A gene. The clinical presentation of TRAPS is heterogeneous, which can complicate its diagnosis. This study aimed to characterize the clinical and genetic features of patients with TRAPS diagnosed and treated in Slovakia, as well as to evaluate their therapeutic response to canakinumab. Materials and Methods: A retrospective analysis of clinical data from the Slovak national database of patients with periodic fever syndromes was performed, including 7 TRAPS patients diagnosed between 2019 and 2022 in Slovakia. These data were compared with findings from available cohorts from Europe, China, and Japan. Results: All 7 patients were female, with a median age at clinical disease onset of 6 years (range: 8 months to 30 years); 1 patient had adult-onset disease. The most frequent symptoms were recurrent episodes of fever (6/7), skin rash (6/7), arthralgia (6/7), myalgia (5/7), abdominal pain (4/7), chest pain (4/7), and general fatigue (4/7). Notably, 1 patient exhibited central nervous system (CNS) involvement manifesting as seizures and aseptic CNS inflammation. Genetic analysis identified 4 variants in TNFRSF1A, including the N145S variant (also referred to as N116S), a variant only rarely reported in the literature. Treatment with canakinumab resulted in a significant reduction in flare frequency and decreases in inflammatory markers. Conclusion: This study underscores the phenotypic diversity of TRAPS, as shown by the identification of the rare TNFRSF1A N145S variant and a case with CNS involvement. The estimated prevalence of TRAPS in Slovakia is approximately 1 : 780 000, and the clinical features of these patients are comparable to those reported in European cohorts. Furthermore, the favorable therapeutic response to canakinumab supports its potential as an effective treatment option for TRAPS.